Severe infections of Panton-Valentine leukocidin positive Staphylococcus aureus in children. Issue 38 (September 2019) - Hoppe, Pia-Alice; Holzhauer, Susanne; Lala, Birgit; Bührer, Christoph; Gratopp, Alexander; Hanitsch, Leif Gunnar; Humme, Daniel; Kieslich, Moritz; Kallinich, Tilmann; Lau, Susanne; Leistner, Rasmus; Niebank, Michaela; et al.
Abstract : Abstract: Infections caused by Panton-Valentine leukocidin-positive Staphylococcus aureus (PVL-SA) mostly present as recurrent skin abscesses and furunculosis. However, life-threatening infections (eg, necrotizing pneumonia, necrotizing fasciitis, and osteomyelitis) caused by PVL-SA have also been reported. We assessed the clinical phenotype, frequency, clinical implications (surgery, length of treatment in hospitals/intensive care units, and antibiotic treatments), and potential preventability of severe PVL-SA infections in children. Total, 75 children treated for PVL-SA infections in our in- and outpatient units from 2012 to 2017 were included in this retrospective study. Ten out of 75 children contracted severe infections (PVL-methicillin resistant S aureus n = 4) including necrotizing pneumonia (n = 4), necrotizing fasciitis (n = 2), pyomyositis (n = 2; including 1 patient who also had pneumonia), mastoiditis with cerebellitis (n = 1), preorbital cellulitis (n = 1), and recurrent deep furunculosis in an immunosuppressed patient (n = 1). Specific complications of PVL-SA infections were venous thrombosis (n = 2), sepsis (n = 5), respiratory failure (n = 5), and acute respiratory distress syndrome (n = 3). The median duration of hospital stay was 14 days (range 5–52 days). In 6 out of 10 patients a history suggestive for PVL-SA colonization in the patient or close family members before hospital admission was identified. PVL-SA causes severe to life-threatening infections requiring lengthy treatments in hospital in a substantial percentage of symptomatic PVL-SA colonized children. More than 50% of severe infections might be prevented by prompt testing for PVL-SA in individuals with a history of abscesses or furunculosis, followed by decolonization measures.